Strategi Pengembangan Bisnis Tanaman Hias PT Monfori Nusantara Dengan Pendekatan Model Bisnis Kanvas - Tiara Sartika Andryana; Heny K. Daryanto; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2019)
The objectives of this study are (1) identifying the business model that is run by PT. Monfori Nusantara with the Canvas Business Model approach; (2) identifying any external and internal factors that affect the business model of the company PT. Monfori Nusantara through SWOT analysis so that alternative strategies are created; (3) Designing a Business Model Canvas repairs as a business development strategy for PT. Monfori Nusantara in the future. The method used was the Canvas Business Model and SWOT. The results of this study are the creation of new values through 9 elements of the Canvas Business Model and strategies such as: expanding the customer segment within the scope of the firm value proposition, increasing efficiency and production capacity, expanding supply propositions, increasing RnD and cost allocation. SWOT analysis on strengths for customer segment elements shows that value propositions and marketing channels have a strong quality relationship with customer segments and products; while the weakness of the customer segment is that the company has not optimized domestic marketing. For the opportunity, the company can utilize the market for plantation crops whereas for the threat, the potential customers can feel bored. PT Monfori Canvas Business Model Improvement produces several targets and developments in each element. The goal of improving each element in the canvas business model aims to expand the potential value propositions that can be offered by PT Monfori.Keywords: business model canvas, floriculture, SWOT, value innovation, tissue cultureAbstrak: Tujuan penelitian ini adalah (1) Mengidentifikasi model bisnis yang dijalankan PT. Monfori Nusantara dengan pendekatan Model Bisnis Kanvas; (2) Mengidentifikasi apa saja faktor eksternal dan internal yang memengaruhi model bisnis perusahaan PT. Monfori Nusantara melalui analisis SWOT sehingga terciptanya alternatif strategi; (3) Merancang Model Bisnis Kanvas perbaikan sebagai strategi pengembangan bisnis PT. Monfori Nusantara di masa depan. Metode yang digunakan adalah Model Bisnis Kanvas dan SWOT. Hasil penelitian ini adalah penciptaan nilai baru melalui 9 elemen Model Bisnis Kanvas dan strategi seperti: memperluas segmen pelanggan dalam lingkup proposisi nilai perusahaan, meningkatkan efisiensi dan kapasitas produksi, memperluas penawaran poposisi, meningkatkan RnD dan alokasi biaya. Analisis SWOT kekuatan untuk elemen segmen pelanggan, proposisi nilai, saluran pemasaran memiliki kualitas hubungan yang kuat dengan segmen pelanggan maupun produk; sedangkan kelemahan segmen pelanggan: belum mengoptimalkan pemasaran domestik; peluang: memanfaatkan pasar tanaman perkebunan; ancaman: calon pelanggan dapat merasa jenuh. Perbaikan Model Bisnis Kanvas PT Monfori menghasilkan beberapa sasaran dan pengembangan pada tiap elemen. Sasaran pada perbaikan tiap elemen pada model bisnis kanvas bertujuan untuk memperluas potensi proposisi nilai yang dapat ditawarkan PT Monfori.Kata kunci: model bisnis kanvas, florikultura, SWOT, inovasi nilai, kultur jaringan